The role of indigenous governance system(s) in sustainable development : a case of Moshupa Village, Botswana - Moatlhaping, Segametsi Oreeditse S. (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MPhil (Sustainable Development, Planning and Management))--University of Stellenbosch, 2007.